A systematic review to explore the feasibility of a behavioural sleep intervention for insomnia in children with neurodevelopmental disorders: A transdiagnostic approach. (October 2018) - Rigney, Gabrielle; Ali, Nicole S.; Corkum, Penny V.; Brown, Cary A.; Constantin, Evelyn; Godbout, Roger; Hanlon-Dearman, Ana; Ipsiroglu, Osman; Reid, Graham J.; Shea, Sarah; Smith, Isabel M.; Van der Loos, Hendrik F.M.; et al.
Summary: Children with neurodevelopmental disorders (NDD) are at high risk for sleep problems, especially insomnia. It is currently not known whether behavioural sleep interventions developed for typically developing (TD) children are effective for children with NDD, and if interventions need to be modified for each diagnostic group. The aim of this systematic review was to identify and evaluate commonalities, trends in outcomes, and the methodological quality of parent-delivered behavioural sleep interventions for children with NDD, specifically Attention-Deficit/Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD), Cerebral Palsy, and Fetal Alcohol Spectrum Disorder. Nine databases were searched. A total of 40 studies met eligibility criteria. The majority of studies were conducted with ASD and ADHD populations. Common sleep problems were evident across the NDD populations. The most frequently reported included bedtime resistance, night-waking, early morning awakening, and co-sleeping. The most common interventions used were implementation of healthy sleep practices, reinforcement, graduated extinction, and faded bedtime. All studies reported at least one behavioural treatment component as effective. Commonalities across NDD populations, as well as the TD population, for both sleep problems reported and behavioural interventions implemented, suggest the feasibility of developing a transdiagnostic behavioural sleep intervention suitable for children with a range of NDD.